The Influence of Economic Conditions on Interest in Continuing Education to Higher Education in Students of SMAN 1 Perhentian Raja, Kampar Regency - Suspita Juliana; Caska Caska; R M Riadi (CV. Rayyan Dwi Bharata, 2023)
This research is motivated by the lack of interest of students to continue their education to tertiary institutions. This study aims to determine the effect of economic conditions on students' interest in continuing their education to tertiary institutions in class XII students at SMAN 1 Perhentian Raja, Kampar Regency. This study uses a quantitative descriptive method. The population in this study were 58 students. The research sample used a census sampling technique. This research data collection method uses a questionnaire / questionnaire. The data analysis technique used is simple regression analysis. Based on the results of the study, it was shown that there was a positive and significant effect of economic conditions on students' interest in continuing their education to tertiary institutions in class XII students of SMAN 1 Perhentian Raja, Kampar Regency.